The relationship between physical activity and psychological sub-health among high altitude region Tibetan college students - Wang, Shoudu; Niu, Zhining; Xiong, Jianping; Chai, Guangxin; Ye, Xingli (Frontiers in Psychology, 2024)
Background The reduction in moderate to vigorous physical activity (MVPA) and the increased prominence of psychological sub-health (PSH) have had a serious negative impact on the health of Tibetan college students. Few studies have been conducted on college student populations at high altitude region in China. Therefore, the study investigated MVPA and PSH in 8721 Tibetan college students to analyze the relationship that exists between them. Methods In this study, subjects were selected by cluster sampling method, and 8,721 high altitude region Tibetan college students were questioned about MVPA, PSH, family situation, BMI, and lifestyle. One-way ANOVA, chi-square test, and stepwise logistic regression analysis were used to analyze the relationship between MVPA and PSH. Results The proportion of Chinese Tibetan college students at high altitude region with MVPA duration ≤30 Mins/Day, 31–60 Mins/Day, and ≥ 61 Mins/Day were 76.7, 18.7, and 4.7%, respectively. The proportion of Tibetan college students in China experiencing PSH was 16.41%. The percentage of emotional symptoms, behavioral symptoms, and social adaptation difficulties were 17.61, 18.04, and 14.59%, respectively. Logistic regression analysis showed that after adjusting for relevant covariates, Tibetan college students with MVPA ≤30 Mins/Day had a higher odds ratio of PSH compared to college male students with MVPA ≥61 Mins/Day (OR = 2.95, 95% CI: 1.79,4.84). In contrast, there was no significant relationship between MVPA and PSH in college females. Overall, Tibetan college students with MVPA ≤30 Mins/Day had a higher odds ratio of PSH compared to Tibetan college students with MVPA ≥61 Mins/Day (OR = 2.99, 95% CI: 2.00,4.47). Conclusion Chinese Tibetan college students from high altitude region areas had lower levels of MVPA and higher rates of PSH. There is an relationship between MVPA time and PSH among high altitude region Tibetan college students, and the incidence of PSH is higher among high altitude region Tibetan college students with shorter MVPA time.